Green Accounting in Romania - a Vision to European Integration - Chirata Caraiani; Mihaela Dumitrana; Corina Dumitru; Mihai Ristea; Cornelia Dascalu; Cleopatra Sendroiu; Raluca Guse; Iulia Jianu; Camelia Lungu; Florian Colceag (European Regional Science Association (ERSA), 2006)
The paper debates solutions, points of view and a commune language for Green Accounting. The main purposes of our research are the following: 1.Define the object of Green Accounting 2.Scope 3.Theory and specific practices 4.Disclosure and financial analysis 5.Romanian experience in Green Accounting. How to define Green Accounting? Is Green Accounting a part of Environmental Accounting? How to ensure the balance between business interests and envinronmental protection? Are environmental goals based on Total Quality Management? How to design for Environment? This are some questions proposed to be discused in this paper.
Keywords: 330